Biomechanics of Cheetah with Applications in Robotics and Athletics - Kherwar, Pramod Kumar; Adhikari, Binilraj; Adhikari, Devendra (Darul Yasin Al Sys, 2024)
The primary emphasis of this article is on cheetahs as fast-moving terrestrial animals whose biomechanics are investigated. An investigation into the biomechanics of this animal provides light on its specialized adaptations that enable to attain extraordinary velocities, thereby shedding light on its evolutionary past and interspecies interactions. Cheetahs have undergone significant physiological, anatomical, and behavioral modifications to accommodate its exceptional speed. The research thoroughly examines the adaptations of the cheetah, encompassing its musculature, talons, and limb structure. Additionally, the respiratory and cardiovascular adaptations that cheetahs possess to facilitate sprinting are discussed in the article. This article also discusses how robot designers and athletes can utilize the strategies used by cheetahs to achieve extremely high speeds through adaptation.